Acute Liver Failure and Hepatic Encephalopathy After Cleft Palate Repair - TUTAR, ENGİN; DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR (ALLIANCE COMMUNICATIONS GROUP DIVISION ALLEN PRESS, 2015)
Paracetamol is the most commonly used analgesic after cleft palate repair. It has rarely caused acute hepatic failure at therapeutic or supratherapeutic doses. Only one case of therapeutic paracetamol toxicity after cleft palate repair had been reported previously. Here, we present a similar patient who developed acute liver failure and hepatic encephalopathy after an uncomplicated cleft palate surgery. Lack of large prospective trials in young children due to ethical concerns increases the value of the case reports of acetaminophen toxicity at therapeutic doses. The dosing recommendations of paracetamol may need to be reconsidered after cleft palate surgery.
Keywords: acetaminophen toxicity; cleft palate; encephalopathy; liver failure; paracetamol; PARACETAMOL; CHILDREN